Evaluation of Bond Strength and Dimensional Accuracy of Soft Liner to Microwave Cured Denture Base Material - Shilan H. Fatah; Radhwan H. Hasan (Polytechnic Journal)
Today, soft liners are being widely used in dental practices by their application to the inner surfaces of the denture with hopes to evenly distribute any potential uneven forces, and to provide a cushion effect to the oral mucosa of the patient mouth. The aim of this study is to investigate the influence of (a) polymethylmethacrylate (PMMA) denture base material curing technique, (b) Molloplast B soft liner curing technique, and (c) PMMA surface treatment, on the “shear bond strength” (SBS) between the Molloplast B liner and PMMA. A total of 80 samples were used in this study to evaluate the SBS performance of microwave (Nature-Cryl, Acron Gc, Japan) and conventional water bath (Ivoclar triplex, Liechtenstein) curing techniques of PMMA, and to evaluate the curing technique of soft liner material Molloplast B (DETAX,GERMANY). Surface treatment of PMMA was performed for half of the samples using neodymium:yttrium aluminum-garnet Nd:YAG laser, and the other half of the samples were surface-treated using AL2O3 sandblasting method. The results showed that the highest mean value in conventional water bath-cured soft liner was 26.69 MPa, whereas the lowest mean value for microwave-cured soft liner was 15.22 MPa. No significant difference was observed between the SBS performance regarding the PMMA surface treatment and curing techniques. Conventional water bath curing technique for soft liner treatment improved the SBS performance. Regarding the PMMA curing technique, the conventional water bath achieved higher SBS, yet the difference was not statistically significant. Finally, surface treatment using laser improved the SBS compared to sandblasted method, but the improvement here was also statistically insignificant.